Pengaruh Kepemilikan Institusional dan Struktur Modal Terhadap Kinerja Keuangan - Zainal Abidin Putera, Fairuz Zabady (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
Fluctuations in coal prices during 2012 - 2019 have an impact on the company's financial performance. Companies are required to evaluate and analyze their financial performance. Many factors affect the company's financial performance. The level of control over management and accountability for financial statements is one of the supervisory efforts that can improve financial performance. This can also suppress managers' tendency to take opportunistic actions for their own interests, which can lead to agency conflicts. The purposes of this research are to analyze the effect of institutional ownership, capital structure, PSAK No. 64, and PP No. 78 / 2010 on the financial performance of Coal Mining Companies listed on the Indonesia Stock Exchange. The type of research is quantitative research. The unit of analysis of this research is the financial reports of listed coal companies on the Indonesia Stock Exchange for 2012 - 2019.The research results showed that the capital structure has a significant and negative effect on financial performance. In contrast, institutional ownership is insignificant and has a positive impact, while PSAK no. 64 and PP. No. 78/2010 has a negligible and negative effect on financial performance.